SHADING AND DEFOLIATION STRESSES ON CARIOCA DRY BEANS CULTIVAR YIELD AND COMPONENTS - DAROS, Edelclaiton; RONZELLI JÚNIOR, Pedro; COSTA, José Antonio; KOEHLER, Henrique Soares (Scientia Agraria, 2000)
During the growing season of 1995/96 and 1996/97, there were carried out field experiments in The Cangüiri Experimental Station of the Federal University of Paraná, Pinhais, PR. The objective was to better ascertain the influence of shading and defoliation stresses in the compensation mechanism of beans, cultivar Carioca, causing reduction on yield and yield components, and also on the apparent harvest index. The experimental design used was the randomized blocks with three replications, on factorial arrangement of treatments 3x7 [check and stresses by shading and defoliation on seven development stages (V2 to R8)]. For the shading stress black shadow screen (sombrite) was used, defoliation was done by cutting the leaves. In both years were evaluated, yield and yield components (averages of pods per plant, seeds per pod, and of 100 seeds weight), and apparent harvest index. In 1996/97 yield components were evaluated separately in stem and branches. The stresses affected the source-sink relationship, resulting in yield reduction, with the highest losses being caused by defoliation. The average number of pods per plant was the better indicator of the stresses effect, being the number of pods on the stem a better indicative then the number of pods on branches. The apparent harvest index was affected by defoliation in 1995/96, and by both defoliation and shading in 1996/97. The stress caused by shading was more effective in causing yield and yield components reduction when applied during the vegetative stages, and the defoliation during the reproductive stages.